Optimal placement and sizing of dgs in distribution networks using mlpso algorithm - Karunarathne E.; Pasupuleti J.; Ekanayake J.; Almeida D. (MDPI AG, 2023)
Particle size analysis; Particle swarm optimization (PSO); Active power loss minimizations; Comprehensive performance; Exponential increase; Optimal placement and sizings; Optimization algorithms; Optimization techniques; Pre-mature convergences; Unity power factor; Electric power transmission networks